Enhancement of magnetocaloric properties in (1 − x)La0.7Ca0.2Sr0.1MnO3/xLa0.7Ca0.15Sr0.15MnO3 composite system (0 ≤ x ≤ 1). (November 2017) - Ezaami, A.; Ouled Nasser, N.; Cheikhrouhou-Koubaa, W.; Cheikhrouhou, A.
Graphical abstract: Highlights: The parent compounds were elaborated by solid-state reaction. Continuous curves were investigated by the numerical calculations in (1 − x)La0.7 Ca0.2 Sr0.1 MnO3 /xLa0.7 Ca0.15 Sr0.15 MnO3 system. The optimum magnetocaloric effect has been found for the composition with x = 0.45. Abstract: The present work reveals an especial agreement between the experimental results and the continuous curves investigated by the numerical calculations in (1 − x)La0.7 Ca0.2 Sr0.1 MnO3 /xLa0.7 Ca0.15 Sr0.15 MnO3 composite system. Moreover, the ability to adjust the magnetic entropy change in a large temperature range is revealed to be possible by the mixture of both individual phases La0.7 Ca0.2 Sr0.1 MnO3 and La0.7 Ca0.15 Sr0.15 MnO3 . Our samples have been synthesised using the solid state method. Rietveld refinements of the X-ray diffraction patterns show that both samples are single phase. The Curie temperature TC is found to be 308 K and 338 K for La0.7 Ca0.2 Sr0.1 MnO3 and La0.7 Ca0.15 Sr0.15 MnO3, respectively. Moreover, the magnetic entropy change and the Relative Cooling Power (RCP) values were estimated. We have shown that the optimum magnetocaloric effect at μ0 H = 2T has been found for the composition with x = 0.45, which exhibits a table-like ΔS curve with a peak value slightly lowered and strongly expanded when comparing with the parent compounds.